2015
DOI: 10.1167/iovs.14-15971
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of Idiopathic Epiretinal Membranes and In Vitro Studies on the Effect of TGF-β on Müller Cells

Abstract: Type VI collagen and activated retinal Müller cells are present in iERM. Transforming growth factor-β1 induces an up-regulation of α-SMA stress fibers in retinal Müller cells and fibroblasts and appears to have a cell-specific effect on intracellular collagen expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 43 publications
2
55
0
10
Order By: Relevance
“…According to previous reports, Müller glial cells and myofibroblasts constituting iERM tissues were positive for glial fibrillary acid protein (GFAP) and α-smooth muscle actin (α-SMA), respectively81516. Double labeling experiments revealed co-localization of (P)RR signal with GFAP, a glial cell marker (Fig.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…According to previous reports, Müller glial cells and myofibroblasts constituting iERM tissues were positive for glial fibrillary acid protein (GFAP) and α-smooth muscle actin (α-SMA), respectively81516. Double labeling experiments revealed co-localization of (P)RR signal with GFAP, a glial cell marker (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Histological analyses of iERM tissues indicated a variety of cells including glial cells, hyalocytes, fibroblasts and myofibroblasts181920. Among them, Müller glial cells, a main constituent cell type in iERM, are the most important cellular components required for membrane growth by intracellular signal transduction1519. Several studies described the involvement of cytokines and trophic factors in the pathogenesis of iERM4816212223.…”
Section: Resultsmentioning
confidence: 99%
“…Transforming growth factor-b induces the differentiation of these cells into a fibroblast-like phenotype and promotes their migration. 7,8 Characteristic cytokine profiles for the differentiation of fibroblasts and retinal glia are unknown, but we assume activated fibroblasts as a source, but not so evidently Müller glia cells, in the chronic phase of ERM formation. The cytokine profiles in our study are commensurate with an activation of fibrotic and inflammatory processes, which are associated with elevated levels of IL-6, IL-4, IL-1b, TNF-a, IL-10, IL-2, and INF-c (among others).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5 Müller glial cells are known to activate fibroblasts and to promote fibrotic changes within the eye, such as proliferative vitreoretinopathy (PVR) 3,6 and the formation of epiretinal membranes (ERMs). 7,8 Epiretinal membranes are characterized by the growth of fibrocellular tissue along the inner limiting membrane (ILM), which can lead to metamorphopsia and visual loss. The most frequently encountered, so-called idiopathic ERMs, are not linked to any other ocular disease process and their pathogenesis remains unidentified.…”
mentioning
confidence: 99%
“…Previous studies revealed that retinal Müller glial cells are involved in the development and progression of ERM. 6,19,20 We also found GS(þ) Müller glial cells made up various proportions of the overall cell population, and part of these cells costained with Gli1. Müller glial cells can act as a source of proliferating progenitors to regenerate neurons in birds, 18 zebrafish, 21 and rodents, 22,23 and which can be activated by Shh signaling.…”
Section: Discussionmentioning
confidence: 51%